Downregulation of FoxC2 Increased Susceptibility to Experimental Colitis: Influence of Lymphatic Drainage Function?. Issue 6 (June 2015) - Becker, Felix; Potepalov, Sergey; Shehzahdi, Romana; Bernas, Michael; Witte, Marlys; Abreo, Fleurette; Traylor, James; Orr, Wayne A.; Tsunoda, Ikuo; Alexander, Jonathan Steven
Abstract : Background: Although inflammation-induced expansion of the intestinal lymphatic vasculature (lymphangiogenesis) is known to be a crucial event in limiting inflammatory processes, through clearance of interstitial fluid and immune cells, considerably less is known about the impact of an impaired lymphatic clearance function (as seen in inflammatory bowel diseases) on this cascade. We aimed to investigate whether the impaired intestinal lymphatic drainage function observed in FoxC2 (+/−) mice would influence the course of disease in a model of experimental colitis. Methods: Acute dextran sodium sulfate colitis was induced in wild-type and haploinsufficient FoxC2 (+/−) mice, and survival, disease activity, colonic histopathological injury, neutrophil, T-cell, and macrophage infiltration were evaluated. Functional and structural changes in the intestinal lymphatic vessel network were analyzed, including submucosal edema, vessel morphology, and lymphatic vessel density. Results: We found that FoxC2 downregulation in FoxC2 (+/−) mice significantly increased the severity and susceptibility to experimental colitis, as displayed by lower survival rates, increased disease activity, greater histopathological injury, and elevated colonic neutrophil, T-cell, and macrophage infiltration. These findings were accompanied by structural (dilated torturous lymphatic vessels) and functional (greater submucosal edema, higher immune cell burden) changes in the intestinal lymphatic vasculature. Conclusions: These results indicate that sufficient lymphatic clearance plays a crucial role in limiting the initiation and perpetuation of experimental colitis and those disturbances in the integrity of the intestinal lymphatic vessel network could intensify intestinal inflammation. Future therapies might be able to exploit these processes to restore and maintain adequate lymphatic clearance function in inflammatory bowel disease. Abstract : Article first published online 27 March 2015.